Three-year durable efficacy of dolutegravir plus lamivudine in antiretroviral therapy – naive adults with HIV-1 infection. (1st January 2022) - Cahn, Pedro; Sierra Madero, Juan; Arribas, José R.; Antinori, Andrea; Ortiz, Roberto; Clarke, Amanda E.; Hung, Chien-Ching; Rockstroh, Jürgen K.; Girard, Pierre-Marie; Sievers, Jörg; Man, Choy Y.; Urbaityte, Rimgaile; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To assess efficacy and safety of dolutegravir (DTG) + lamivudine (3TC) vs. DTG + tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) in treatment-naive adults with HIV-1 in the prespecified 144-week secondary analyses of GEMINI-1 and GEMINI-2. Design: Identical, multicenter, phase III, randomized, non-inferiority studies (double-blind through 96 weeks). Methods: Participants with HIV-1 RNA ≤500 000 copies/ml and no major viral resistance mutations to nucleoside reverse transcriptase inhibitors, nonnucleoside reverse transcriptase inhibitors, or protease inhibitors were randomized 1:1 to once-daily DTG + 3TC or DTG + TDF/FTC. Results: At week 144, DTG + 3TC ( N = 716) was noninferior to DTG + TDF/FTC ( N = 717) in proportion of participants achieving HIV-1 RNA <50 copies/ml (Snapshot algorithm) in the pooled analysis (82% vs. 84%, respectively; adjusted treatment difference [95% confidence interval (CI)], −1.8% [−5.8, 2.1]), GEMINI-1 (−3.6% [−9.4, 2.1]), and GEMINI-2 (0.0% [−5.3, 5.3]). Twelve DTG + 3TC participants and nine DTG + TDF/FTC participants met protocol-defined confirmed virologic withdrawal (CVW) criteria; none developed treatment-emergent resistance. One DTG + 3TC participant who did not meet CVW criteria developed M184V at week 132 and R263R/K at week 144, conferring a 1.8-fold change in susceptibility to DTG; non-adherence to therapy was reported. Significantly fewer drug-related adverse events occurred with DTG + 3TC vs. DTG + TDF/FTC (20% vs. 27%; relative risk [95% CI], 0.76 [0.63–0.92]). Renal and bone biomarker changes favored DTG + 3TC. Conclusions: Three-year durable efficacy, long-term tolerability, and high barrier to resistance support first-line use of DTG + 3TC for HIV-1 treatment (see Supplemental Digital Content 1, http://links.lww.com/QAD/C297 ; video abstract).